Dataset from dried blood spot acylcarnitine for detection of Carnitine-Acylcarnitine Translocase (CACT) deficiency and Carnitine Palmitoyl Transferase 2 (CPT2) deficiency - Anasufiza Habib; Muhammad Irfan Bukhari Ahmad Nazri; Salina Abdul Rahman (Data in Brief, 2023)
Clinical diagnosis of inborn errors of metabolism in the suspected patients is usually guided by the initial general investigations in the laboratory such as the concentration of ammonia, blood gases status, blood glucose and ketones. The establishment of a biochemical diagnosis in patients with inborn errors of metabolism depends on the detection of the specific metabolites in the abnormal metabolic pathway which can appear in any of the body fluids but are most commonly tested in blood and urine samples. Acylcarnitine and/or acylcarnitine ratio in patients with carnitine acylcarnitine translocase and carnitine palmitoyl transferase deficiency showed an abnormal profile regardless of the metabolic status of patients. The acylcarnitine was derived from the analysis of dried blood spot using multiple reaction monitoring (MRM) which was performed using quadrupole mass spectrometry. The dataset presented in this article was generated from analysis of acylcarnitines in the 17,121 dried blood spots from symptomatic Malaysian patients less than fifty years old who exhibited symptoms suggestive of inborn errors of metabolism, but had a normal acylcarnitine profile. A precursor or ion scan of m/z 85 was selected for the analysis. Quantification of each analyte was obtained using the signal intensity ratio of the acylcarnitine to its internal standard. The acylcarnitines analyzed included C0, C2, C3, C3DC, C4, C5, C5:1, C5DC, C5OH, C6, C8, C10, C12, C14, C16, C18, C18:1, C16OH, C18OH and C18:1OH and was analyzed using Neolynx V4.0 software. We decided to choose the 1st and 99th percentiles as the minimum and maximum cut-offs. The filtered part of data in this article was used in the article Novel mutations associated with Carnitine-Acylcarnitine Translocase and Carnitine Palmitoyl Transferase 2 deficiencies in Malaysia. This dataset is intended to enable the scientific communities to get access to the raw dataset for future translational research use in inborn errors of metabolism as very few acylcarnitine data was developed and published for the symptomatic patients suspected of inborn errors of metabolism especially in the Asian population.